Subordination vs. agency/resistance in South Africa: Virgins bargaining their way through higher education - Stander, Sunelle (Stellenbosch theological journal, 2016)
Oppression manifests itself in various ways, such that intersections between different forms of oppression can be identified. This is also true for women living in South Africa, a country that has for years been plagued by many forms of oppression (racism, sexism, classism, etc.). Women are, amidst various forms of oppression, often left with few alternative options but to bargain with various forms of gender relations as a means to obtain basic human rights (like education). Recent student protests have highlighted the discriminating ways in which black students are kept from obtaining higher education. The so called “maidens bursary”, awarded to underprivileged girls who vow to stay virgins throughout their studies, will be used as a case study that examines an alternative route to which underprivileged women may resort in order to obtain a quality education. The notion of patriarchal bargaining will then be used to illumine the often unrecognized, complex and interwoven relationship between subordination and agency/resistance that operates within the South African context.